2011
DOI: 10.1111/j.1502-3885.2011.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope evidence of last glacial climate variations in the tropical NW Leizhou Peninsula, South China

Abstract: Bulk organic d 13 C values of sediment sequences are commonly used to indicate past climatic changes, although the causes and mechanisms leading to the observed organic carbon isotope responses are presently not fully understood. Based on two sedimentary sequences, namely a peat profile and a fluvial and swamp sequence from the tropical NW Leizhou Peninsula in South China, we interpret more negative bulk organic d 13 C values to suggest wetter and warmer conditions, implying a stronger East Asian (EA) summer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The Leizhou Peninsula is located at the northern boundary of the Tropic of Capricorn in South China (Figure 1). The precipitation in this region is strongly influenced by the East Asian summer monsoon and, to a lesser extent, by the Indian summer monsoon [17]. This area, along with the entire South China Sea, provides the moisture supply for the summer monsoon rainfall throughout the eastern part of China from June to August and has a rich average annual rainfall of 1400 mm, with approximately 75% of the precipitation falling during this rainy season.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Leizhou Peninsula is located at the northern boundary of the Tropic of Capricorn in South China (Figure 1). The precipitation in this region is strongly influenced by the East Asian summer monsoon and, to a lesser extent, by the Indian summer monsoon [17]. This area, along with the entire South China Sea, provides the moisture supply for the summer monsoon rainfall throughout the eastern part of China from June to August and has a rich average annual rainfall of 1400 mm, with approximately 75% of the precipitation falling during this rainy season.…”
Section: Site Descriptionmentioning
confidence: 99%
“…The Leizhou Peninsula is an ideal site for investigating volcanic hydrogeological environments [17]. A recent study indicated that groundwater contains low total dissolved solids (TDS) (ranging from 40 to 550 mg/L), is weakly acidic, and has a low pH between 4 and 7 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although studies of δ 13 C for individual peatlands have been conducted (e.g. [1,2,8,18,27,28,29]), we propose that a constant δ 13 C value is adequate for a first-order understanding of carbon isotope composition of peatlands and sufficient for showing the benefit of the method. We use the mean 13 C from these studies, −25 .…”
Section: Adding a Net Carbon Sinkmentioning
confidence: 96%
“…Based on two peat successions obtained in the Zhanjiang district in western WGDP, the evolutionary history of the ASM in the past c. 50 000 years has been reconstructed using organic carbon isotopes (Zhong et al . ), pollen data (Xue et al . ) and the charcoal record (Xue et al .…”
mentioning
confidence: 99%
“…Several studies have been performed on the late Late Pleistocene climatic changes in WGDP. Based on two peat successions obtained in the Zhanjiang district in western WGDP, the evolutionary history of the ASM in the past c. 50 000 years has been reconstructed using organic carbon isotopes (Zhong et al 2012), pollen data (Xue et al 2015a) and the charcoal record (Xue et al 2015b). Yancheva et al (2007) reconstructed the strength of the Asian winter monsoon winds over the past 16 000 years using the magnetic properties and the titanium content of sediments from Lake Huguang in the Leizhou Peninsula.…”
mentioning
confidence: 99%